2021
DOI: 10.2340/16501977-2828
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with met and unmet rehabilitation needs after stroke: A multicentre cohort study in Denmark and Norway

Abstract: Objectives To examine patient-reported needs for care and rehabilitation in a cohort following different subacute pathways of rehabilitation, and to explore factors underpinning met and unmet needs. Design Observational multicentre cohort study. Patients and methods A total of 318 Norwegian and 155 Danish patients with first-ever stroke were included. Participants answered questions from the Norwegian Stroke Registry about perceived met, unme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
(54 reference statements)
1
2
0
Order By: Relevance
“…The observed prevalence of unmet rehabilitation needs was 32.6%, which is consistent with a previously reported range of 15%-33% (7,2224). In a study by Ullberg et al, female sex, living alone, smoking, atrial fibrillation, diabetes, somnolence, comatose status, prior stroke, and intracranial hemorrhage or unspecified stroke were all associated with an increased OR for unmet rehabilitation needs (7).…”
Section: Discussionsupporting
confidence: 91%
“…The observed prevalence of unmet rehabilitation needs was 32.6%, which is consistent with a previously reported range of 15%-33% (7,2224). In a study by Ullberg et al, female sex, living alone, smoking, atrial fibrillation, diabetes, somnolence, comatose status, prior stroke, and intracranial hemorrhage or unspecified stroke were all associated with an increased OR for unmet rehabilitation needs (7).…”
Section: Discussionsupporting
confidence: 91%
“…As discussed by Heiberg et al [ 25 ], in the broad geographic rural North Norwegian region, available specialized subacute inpatient rehabilitation services are necessary. Parallel with building systems for improved transitions from stroke units and rehabilitation units to home, improved follow-up of persons with PSCI in the municipalities is further required.…”
Section: Discussionmentioning
confidence: 99%
“…In Norway, rehabilitation usually takes place in hospitals [ 23 ], where most acute stroke patients (95%) are admitted to stroke units [ 24 ]. A recent study from the northern part of Norway showed that approximately 40% of participants received further inpatient treatment at rehabilitation units, 17% received community-based rehabilitation, and 43% received no rehabilitation after discharge from stroke units [ 25 ]. However, this study revealed little about the content of professional support for community-based services or which kind of patients' needs these services applied to.…”
Section: Introductionmentioning
confidence: 99%